A Water Dissolvable Electrolyte with an Ionic Liquid for Eco‐Friendly Electronics. Issue 32 (21st June 2018) - Yamada, Shunsuke; Toshiyoshi, Hiroshi
Abstract: A water‐dissolvable electrolyte is developed by combining an ionic liquid (IL) with poly(vinyl alcohol) (PVA), which decays over time by contact with water. An IL generally consists of two species of ions (anion and cation), and forms an electrical double layer (EDL) of a large electrostatic capacitance due to the ions accumulated in the vicinity of a conductive electrode when voltage is applied. In a similar manner, the ionic gel developed in this work forms an EDL due to the ions suspended in the conjugated polymer network while maintaining the gel form. Test measurements show a large capacitance of 13 µF cm −2 within the potential window of the IL. The ionic gel shows an electrical conductance of 20 µS cm −1 due to the ionic conduction, which depends on the weight ratio of the IL with respect to the polymer. The developed ionic gel dissolves into water in 16 h. Potential application includes the electrolyte in disposable electronics such as distributed sensors and energy harvesters that are supposed to be harmless to environment. Abstract : A water‐dissolvable electrolyte is developed by combining an ionic liquid with poly(vinyl alcohol), which decays over time by contact with water. Test measurements show a capacitance of 13 µF cm −2 and an electrical conductance of 20 µS cm −1 . Potential applications includes the electrolyte in disposable electronics such as distributed sensors and energy harvesters that are supposed to be harmless to the environment.